Apparent Molar Volume Studies of Triton X-100 in Aqueous and Mixed Solvents - K. Yadav, Satyender (Asian Journal of Chemistry, 2011)
In the present study densities of Triton X-100 + water, Triton X-100 + water + propanol and Triton X-100 + water + fructose have been measured at different concentrations and temperatures. Apparent molar volumes have been calculated for the studied systems from density values to study the effect of added co-solute/co-solvent on the structure of the studied systems. The apparent molar volumes in Triton X-100 + water + additive (2- propanol/fructose) systems are found to be less than in Triton X-100 + water system. This is attributed to entrapping, as well as hydrogen bonding. With increase of temperature the apparent molar volume (fv) values increase in all the studied systems, owing to breaking of water structure at higher temperature.